(3JhVjM GdJPcQI (B_ (3aj Yde GdgjFIs - (3GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQqi, fXGe GdOjf, hjbGd dg GdCYQL ` HYO (B850 (3g` s; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s
(3ChdgG (B:s
(3hHYO , jbhd (B: (3ef GdeYdhe Cf GdYdhe JJHGjf ai GdTQa HMSH JHGjf ehVhYGJgG hgh Yde gjFI GdCadGc hCf cJGH GdJPcQI ai gPG Gdaf GdefShH Edi GdWhSi Cf CcJH ajg TQMkG jPdd ef GddaX UhGHg s
(3BNQgG (B:s
(3aEf GdCYeGd HGdfjGJ , hHgG JLdH GdHQcGJ , hJfGd GdOQLGJ , hGdMeO ddg deHOY Gdcd hbO EJab aQGZi ef JCdja gPG GdcJGH s
(3HgG CTcGd hQShes
(3HgG fXGe GdJYbjHIs
(3fSNI KGdKIs
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ ai HYV GdCdaGX s
(3cJHJ Hbde eged GdfbW CMjGfkG s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs